2017
DOI: 10.21511/ppm.15(4).2017.08
|View full text |Cite
|
Sign up to set email alerts
|

Econometric analysis of the structure and sustainability of Ukraine socio-economic system in the context of the economic systems theory

Abstract: The article is devoted to the development of a conceptually new systemic structural approach to the study of sustainability of economic systems. The problem of ensuring sustainability of economic entities remains unsolved, largely due to the lack of the necessary methodology. In the article, the approach is shaped by new economic systems theory, which implies the division of all economic systems into types depending on their spatiotemporal localization. Applied research of socio-economic system of Ukraine in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…As a result of our own studies, we confirmed the hypothesis that the economic sustainability of the system was caused by the structural balance of its subsystems with different space-time localization on the example of economic systems of macroand microlevels. Besides, according to its results, some provisions of systemic economic theory were checked and partially refined (Kravchenko, 2016, Dergachova et al, 2017. According to the hypothesis, the level of economic system sustainability can be determined through assessing the level of mutual balance of its four subsystems.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of our own studies, we confirmed the hypothesis that the economic sustainability of the system was caused by the structural balance of its subsystems with different space-time localization on the example of economic systems of macroand microlevels. Besides, according to its results, some provisions of systemic economic theory were checked and partially refined (Kravchenko, 2016, Dergachova et al, 2017. According to the hypothesis, the level of economic system sustainability can be determined through assessing the level of mutual balance of its four subsystems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the hypothesis, the level of economic system sustainability can be determined through assessing the level of mutual balance of its four subsystems. The methods and results of assessing the level of sustainability of social and economic system of Ukraine as a system of macrolevel according to such approach are presented in Dergachova et al (2017), the methods and results of assessing the sustainability of enterprises as systems of microlevel -in Kravchenko (2016). This research focuses on more deep economic analysis of the defined structural peculiarities of the enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Також пропонується три принципи згідно з якими має здійснюватись регулювання [29]. По-перше, регулювання повинно ґрунтуватися на загальній структурі правил між національними юрисдикціями.…”
Section: джерело: складено автором за результатами дослідженняunclassified
“…КЛЮЧОВІ СЛОВА: сталий розвиток, економічне зростання, ВВП, доходи на одного працюючого, національне господарство, викиди забруднюючих речовин Горошкова Л. А. 1 Методы. Общенаучные (анализ и синтез, индукция и дедукция, аналитическое группировки) и специальные (абстрагирование, моделирование и т.…”
unclassified